ENGLISH LANGUAGE TEACHING IN THE INDONESIAN CONTEXT TOWARD EDUTECH 4.0 - Morin Oktavia; Noviati Noviati; Ana Theriana; Aswadi Jaya (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2021)
Edutech or Educational Technology refers to the process of the study facilitated by technology.  It allows teachers and students to use everyday devices such as smartphones, laptops, and tablets. The objectives of this study were to find out significant challenges that created the educational technological immersion for English language teaching and to identify the way junior high school English teachers of one public school in Pangkalpinang adapted to the Edutech 4.0. This study applied Qualitative Design in which the informants of this study were the principals, English teachers, and the students. The data were collected by using observation, interview, and questionnaire. Based on the result, it showed that the teachers could easily adapt to the Google Suites for Education and all of the teachers were comfortable in using Google Suites for Education as the Edutech, but they still found it difficult to interact with the students.